Digitalisasi Pemasaran dan Optimalisasi Manajemen Keuangan Guna Meningkatkan Pendapatan Tap Tan Dapoer Levis - Heni Purwantini; Destin Alfianika Maharani; Hasirun; Meliana Cintia Sari; Sidiq Ali Mustofa (Jurnal Pemberdayaan Masyarakat, 2025)
UMKM play an important role in economic growth. The existence of UMKM is a business that is able to demonstrate competitive advantages and dynamics in economic growth. This community service was carried out at an UMKM that produces sticky rice tape under the brand name Dapoer Levis in Purbalingga. The objective of this community service is focused on financial management as an effort to increase creative economic growth and employment, as well as digital marketing aspects to promote inclusive products, foster sustainable product innovation, and increase income. The community service method was divided into three stages: the first stage was preparation for observation, the second stage was implementation consisting of socialization activities, workshops, and financial management and digital marketing assistance, and the third stage was evaluation to ensure that the community service could be implemented appropriately. The results of the community service are to increase knowledge and facilitate financial record management using digital financial applications and the use of website technology and marketplace applications to expand product marketing with the aim of increasing income.